Effects of dietary intake behavior, food supply, nutrition, and health during the COVID-19 outbreak - Roy, Pantu Kumar; Song, Min Gyu; Jeon, Eun Bi; Kim, So Hee; Park, Shin Young (Frontiers in Sustainable Food Systems, 2022)
The coronavirus disease 2019 (COVID-19) pandemic, which began in 2019, has massive ramifications, including economic losses and health challenges that still affect various parts of the world. This review inspects the effect of severe acute respiratory syndrome 2 (SARS-CoV-2) infection, the source of COVID-19, on the food supply chain, food safety, dietary habits, nutrition, and health. The COVID-19 pandemic has ushered in a new era in the food sector. During our reviewing, the entire world is working to stop the spread of the SARS-CoV-2 outbreak. Thus, assessing the potential effect of this virus on food safety is critical for authorities, the food industry, and people, including their nutrition and health. During the COVID-19 pandemic, there were modifications in food consumption. Its goal is to map changes in individual consumer food consumption and determine the impact of various COVID-19 pandemic-related parameters. Restrictions imposed in response to the pandemic (e.g., closure of physical work-places, canteens, cafes and restaurants, schools, and childcare institutions), changes in household grocery shopping frequency, individuals' perceived risk of COVID-19, income losses due to the pandemic, and socio-demographic factors are among the factors. The conclusions discuss the implications of healthy diets, food system resilience, behavior change, and nutritional imbalance for policymakers and food supply chain participants and antimicrobial effects of vitamin ingredients. Concerns about food and nutrition during the post-lockdown period were common and were linked to dietary behavior changes. In order to reduce incorrect eating behaviors during public health crises, preventative policies and nutritional advice should be devised to address these problems.